Radhika Borde, Alison A. Ormsby, Stephen M. Awoyemi, and Andrew G. Gosler (eds.), Religion and Nature Conservation: Global Case Studies - Rabin, Joel Elliott (Journal for the study of religion, nature and culture, 2025)
Radhika Borde, Alison A. Ormsby, Stephen M. Awoyemi, and Andrew G. Gosler (eds.), Religion and Nature Conservation: Global Case Studies (New York: Routledge, 2023), 350 pp., $ 48.99 (pbk), ISBN: 9781032158990.